2009
DOI: 10.5248/109.103
|View full text |Cite
|
Sign up to set email alerts
|

<I>Septobasidium maesae</I> sp. nov. (<I>Septobasidiaceae</I>) from China

Abstract: A new species, Septobasidium maesae on Maesa perlarius associated with Pinnaspis sp. and Diaspidiotus sp. (Diaspididae), is described. It was collected from Wuzhi Mountain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…To date, 29 species of Septobasidium have been reported in China (Sawada 1933, Couch 1938, Teng 1963, Tai 1979, Kirschner & Chen 2007, Lu & Guo 2009a,b,c, 2010a,b,c, Lu et al 2010, including the new species reported in this paper.…”
Section: Figs 1-7mentioning
confidence: 64%
“…To date, 29 species of Septobasidium have been reported in China (Sawada 1933, Couch 1938, Teng 1963, Tai 1979, Kirschner & Chen 2007, Lu & Guo 2009a,b,c, 2010a,b,c, Lu et al 2010, including the new species reported in this paper.…”
Section: Figs 1-7mentioning
confidence: 64%
“…To date, 23 species of Septobasidium have been reported in China (Sawada 1933, Couch 1938, Teng 1963, Tai 1979, Kirschner & Chen 2007, Lu & Guo 2009a, b,c, Lu et al 2010, including the three species reported in this paper.…”
Section: Excluded Speciesmentioning
confidence: 65%
“…Nevertheless, the species could not be identified. Recently, morphological characteristics and host information of more than 20 species of Septobasidium have been introduced from China [ 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 ], Costa Rica [ 28 29 ], and the southeastern United States [ 29 ]. Unfortunately, most Septobasidium spp.…”
Section: Identification and Discussionmentioning
confidence: 99%